Leishmania infantum arginase: biochemical characterization and inhibition by naturally occurring phenolic substances. (1st January 2019) - Garcia, Andreza R.; Oliveira, Danielle M. P.; Claudia F. Amaral, Ana; Jesus, Jéssica B.; Rennó Sodero, Ana Carolina; Souza, Alessandra M. T.; Supuran, Claudiu T.; Vermelho, Alane B.; Rodrigues, Igor A.; Pinheiro, Anderson S.
Abstract: Inhibition of Leishmania arginase leads to a decrease in parasite growth and infectivity and thus represents an attractive therapeutic strategy. We evaluated the inhibitory potential of selected naturally occurring phenolic substances on Leishmania infantum arginase (ARGLi) and investigated their antileishmanial activity in vivo . ARGLi exhibited a V max of 0.28 ± 0.016 mM/min and a K m of 5.1 ± 1.1 mM for L-arginine. The phenylpropanoids rosmarinic acid and caffeic acid (100 µM) showed percentages of inhibition of 71.48 ± 0.85% and 56.98 ± 5.51%, respectively. Moreover, rosmarinic acid and caffeic acid displayed the greatest effects against L. infantum with IC50 values of 57.3 ± 2.65 and 60.8 ± 11 μM for promastigotes, and 7.9 ± 1.7 and 21.9 ± 5.0 µM for intracellular amastigotes, respectively. Only caffeic acid significantly increased nitric oxide production by infected macrophages. Altogether, our results broaden the current spectrum of known arginase inhibitors and revealed promising drug candidates for the therapy of visceral leishmaniasis.